Outcomes of tricuspid transcatheter edge-to-edge repair in subjects with endocardial leads - Goebel, Björn; Lurz, Philipp; Schmitz, Thomas; Bekeredjian, Raffi; Nickenig, Georg; Mollmann, Helge; von Bardeleben, Ralph Stephan; Schmeisser, Alexander; Heitkemper, Megan; Atmowihardjo, Iskandar; Estévez-Loureiro, Rodrigo; Donal, Erwan (EuroIntervention : journal of EuroPCR in collaboration with the Working Group on Interventional Cardiology of the European Society of Cardiology, 2025)
Transcatheter edge-to-edge repair (TEER) using the TriClip tricuspid valve repair system has emerged as a therapy for tricuspid regurgitation (TR). Patients with TR undergoing TEER commonly present with an endocardial lead across the tricuspid valve (TV). We sought to examine the effectiveness and safety of tricuspid TEER (T-TEER) in subjects with endocardial leads in the bRIGHT EU Post-Approval Study (PAS). The bRIGHT EU PAS is a prospective, single-arm, open-label, multicentre, post-market registry conducted at 26 sites in Europe. Echocardiographic assessments of endocardial lead placement, interaction, and TR grade were performed at a core laboratory. Of the 511 enrolled subjects, a total of 110 had an endocardial lead, and in 80.7% of these subjects, TR was at least partially related to the lead. At 30 days, 71% of subjects with endocardial leads had TR of moderate or less. The percentage of subjects with endocardial leads categorised as New York Heart Association Functional Class I-II increased from 17% at baseline to 75% at 30 days (p<0.0001), and quality of life with the Kansas City Cardiomyopathy Questionnaire showed a mean improvement of 20±24 points from baseline to 30 days (p<0.0001). T-TEER was safe in subjects with endocardial leads, with similar rates of events, including TV reintervention/reoperation and TV surgery, to those in subjects without leads. No reports of lead malfunction were reported. In the bRIGHT EU PAS, T-TEER using the TriClip system was safe and effective in severe TR subjects with an endocardial lead across the TV.